OC-13 - Safe and effective use of direct oral anticoagulants (DOAC) versus conventional anticoagulation for the treatment of cancer-related venous thromboembolism. Issue 140 (April 2016) - Ross, J.A.; Miller, M.; Rojas-Hernandez, C.M.
Abstract : Introduction: Cancer is a risk factor for the development of venous thromboembolism (VTE). The standard of care for the treatment of cancer-related VTE is a low molecular weight heparin (LMWH) formulation. The treatment for these events can be painful, lengthy, and expensive. The development of DOAC has created new options for the treatment of VTE. Data from a recent systematic review suggested that the safety and effectiveness of DOAC in patients with cancer is equivalent to that of traditional therapies. If equivalent to LMWH, the use of DOAC in the treatment of cancer-related VTE would reduce the risk of VTE recurrence while giving patients freedom from subcutaneous injections. Aim: Our primary aim was to determine the rate of VTE recurrence in patients on anticoagulation. Secondary aims were determination of the rate of anticoagulant-associated clinically relevant bleeding and VTE recurrence-free survival. Materials and Methods: We performed retrospective analysis (2014-2015) of the electronic medical records (EMR) of adult patients with cancer-related VTE treated with anticoagulation. We selected 122 patients for our final analysis according to the inclusion criteria. Demographic, laboratory, cancer diagnosis, and VTE diagnosis data were collected. We documented VTE recurrence as well as clinically relevant bleeding. Non-parametric statistical procedures were used to determine differences in variables associated with this study among the anticoagulant class groups, with a test significance level of 0.05. Results: Among 122 patients, 89 (73%) were treated with LMWH, 26 (21%) were treated with DOAC, and 7 (6%) were treated with warfarin. The majority of VTE occurred in patients with advanced disease. The most common index event was pulmonary embolism (49%) followed by catheter-associated deep venous thrombosis (DVT) (24%). Recurrence of VTE occurred in 7.7% of patients receiving DOAC and 7.9% of patients receiving LMWH (P = NS). Major bleeding occurred more often with the use of DOAC (11.5%) than with LMWH (10.1%), but non-major bleeding was more common in patients receiving LMWH (9.0% versus 7.7%). These differences were not statistically significant. There was no mortality attributed to bleeding complications. The VTE recurrence-free survival rates were not statistically different among LMWH versus DOAC (Figure 1). Fig. 1 Kaplan-Meier curve for VTE recurrence-free survival. Conclusions: Recurrence of cancer-associated VTE is not uncommon, and the treatment of VTE has significant hemorrhagic risks. Our analysis suggests that there is no significant difference in the rate of VTE recurrence and anticoagulant-related bleeding when using oral DOACs versus LMWH. Further studies are needed to compare the safety and effectiveness of these methods of anticoagulation.